Assessment of Dietary Habits in Final Year Medical Students at a Public University Faculty of Medicine in Turkey During COVID-19 - KARAVUŞ, MELDA (My University, 2024)
Introduction: Optimal health depends on the intricate interplay of genetics, environment, and nutrition, encompassing aspects of physical, mental, and social well-being. This study rigorously assesses the dietary habits of final-year medical students during their internship, with a specific focus on understanding the implications of the COVID-19 pandemic. The overarching goal is to advocate for and contribute to the fostering of healthier lifestyles among medical students. Materials/Methods: This descriptive research aimed to survey the entire cohort comprising 200 final-year medical students enrolled in the Faculty of Medicine at a public university. Among them, 125 participants actively participated in the online dietary survey conducted from September to October 2020. Results: During their internship, most participants had two (35.2%) or three (48.8%) daily meals, often skipping breakfast (40.0%) due to lack of appetite or opportunities. Approximately 77% maintained underweight or normal weight. The majority (95.2%) lacked a specific dietary pattern. Protein and carbohydrates were favored (75.3% for females, 96.2% for males), with more females choosing fruits and vegetables. Conclusions: This study underscores the imperative for an all-encompassing nutrition education framework within medical student curricula. It unveils discernible variations in dietary practices, encompassing the consumption of nuts, sugary foods, energy drinks, and tea/coffee, stratified by gender and body mass index. Furthermore, the investigation establishes that exam preparation significantly influences dietary habits. Notably, independent living emerges as a pivotal factor shaping preferences for sugary foods. Keywords: Intern, Medical School, Nutrition, Student
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Intern; Medical School; Nutrition; Student